Upper and Lower Jaw Segmentation in Dental X-ray Image Using Modified Active Contour - Harandi, A. A.; Pourghassem, H.; Mahmoodian, H. (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
Segmentation of dental X-ray images is an important factor in automatic dental identification system (ADIS) application. The first step in the dental X-ray image segmentation is separation of the upper and lower jaw. In this paper, an upper and lower jaw segmentation algorithm based on modified geodesic active contour and morphological operation is proposed. This algorithm is carried out based on applying morphology operation on teeth X-ray image for better separating and then subtracting the image. The geodesic active contours method has been modified for upper and lower segmentation application. Ultimately, the proposed algorithm is evaluated on a standard database of dental X-ray image. The obtained results show effectiveness and efficiency of our proposed algorithm.